Successful treatment of ileofemoral venous thrombosis following cardiac catheterization. Issue 6 (November 1973) - Whittaker, Mark; Kerr, R. V.
Abstract : Whittaker, M., and Kerr, R. V. (1973). Thorax, 28, 794-796. Successful treatment of ileofemoral venous thrombosis following cardiac catheterization. This paper describes a case of ileofemoral venous thrombosis following transseptal cardiac catheterization. The diagnosis was established by phlebography and early venous thrombectomy was successfully performed.